Transition from a spectrum filter to a polarizer in a metallic nano-slit array - Zhou, Jing (Nature Publishing Group, 2014)
The transition from a spectrum filter (resonant transmission) to a polarizer (broadband transmission) for TM polarized light is observed in a metallic nano-slit array as period is decreased. A theoretical model is developed and shows that the spectrum filter behavior is caused by the coupled slit/grating resonance. With decreasing period, the slit resonance is decoupled from the grating resonance, which then dominates the transmission spectrum and broadens the transmission peak. With further reducing period, the slit resonance diminishes and the peak spectrum transforms to a broadband transmission. This effect is the basis for the operation of wire grid polarizers. The transition is explained by the change of the impedance to the incoming wave.